Alternative Livelihood Opportunities for Fishers of Bargi Reservoir, Madhya Pradesh - Nidhi Katre; S.N. Ojha; Arpita Sharma; Rama Sharma; Sona Dubey; Vinod Yadav (Journal of Indian Fisheries Association, 2020)
The study was conducted in 6 fishing villages of the Bargi reservoir of Madhya Pradesh. Focus group discussions and interviews of 180 fishers were used for data collection. To explore the possibilities of adopting the alternative livelihood, in the beginning, the constraints faced by the fishers were ranked using the Rank Based Quotient (RBQ) method. Thereafter, the alternative sources of income practiced by the fishers -to meet their basic needs -were explored. Finally, the fishers’ choice of selecting preferred alternative livelihood options were also collected. The results showed that the majority of fishers were constrained by low income. Financial problems were ranked as the second most persistent constraint among fishers, while poaching and other social problems were the third severe constraint. The economic, environmental, and social constraints identified were lack of financial support through schemes; no credit facility and marketing rights; the decline in the fish catch; conflicts between fishers, outsiders, and fisheries officials; unauthorized marketing of fishes; and illiteracy among fishers. The Alternative Livelihood Options practiced by the fishers were working as wage labourer; farm and construction worker, and growing vegetables. The fishers were observed to prefer some other alternative livelihood such as aquaculture in village ponds, eco-tourism and ornamental fish culture. These findings can help bridge fishers’ preferences for alternative livelihood with diﬀerent welfare schemes of the government.